1993
DOI: 10.1016/0014-5793(93)81461-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and molecular cloning of chymase from human tonsils

Abstract: A chymotrypsin‐like protease was purified to homogeneity from human tonsils by a series of Chromatographie procedures. The purified enzyme gave a single protein band with an apparent molecular mass of 30 kDa on SDS‐PAGE. The sequence of the first 21 amino acids at the N‐terminus of the enzyme was determined. A cDNA for the enzyme was cloned by PCR amplification from extracted tonsillar mRNA using a supposed N‐terminal oligonucleotide primer and a conserved C‐terminal primer of the chymase family. The deduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This discrepancy may be accounted for by one or more of the following differences in chromatographic conditions: matrix (TSK heparin versus heparin-agarose), salt (KCl versus NaCl), pH (8.0 versus 6.8) and Triton X-100 (gradient of 0.0 to 0.1 % versus a constant 0.03%). Chymase from human tonsil tissue has been reported to be eluted from a heparin-agarose column at 1.2 M NaCl [25], the same as chymase B in the present studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This discrepancy may be accounted for by one or more of the following differences in chromatographic conditions: matrix (TSK heparin versus heparin-agarose), salt (KCl versus NaCl), pH (8.0 versus 6.8) and Triton X-100 (gradient of 0.0 to 0.1 % versus a constant 0.03%). Chymase from human tonsil tissue has been reported to be eluted from a heparin-agarose column at 1.2 M NaCl [25], the same as chymase B in the present studies.…”
Section: Discussionsupporting
confidence: 59%
“…Only one form has been purified from skin [24], heart [4] and tonsil [25] tissue. All these isolates appear to have identical amino acid sequences [25Ϫ27], and an identical sequence is also predicted from cDNA from the uterus [28].…”
mentioning
confidence: 99%
“…Since chymase belongs to the chymotrypsin family of protease (Sukenaga et al, ) and chymase‐induced mast cell accumulation may depend on its enzymatic activity, we employed the common chymotryptic enzymes α 1 ‐chymotrypsin (Niemann, ) and elastase as positive and negative controls, respectively, in the present study. The results showed that α 1 ‐chymotrypsin also induced a dose‐dependent increase in mast cell accumulation at 6 h (Figure E) and 16 h (Figure F) following injection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, human chymase activates angiotensin I to angiotensin II by cleavage of a Phe–His bond, but does not degrade angiotensin II by clipping a Tyr–Ile bond, as do chymotrypsin, and chymases from other species [9]. To date, only one chymase gene has been identified in humans [13], although a Cys‐to‐Ser variation at position seven of the mature enzyme has been reported [14]. This is the first report of crystallization of human chymase.…”
Section: Introductionmentioning
confidence: 99%